Diet and erythrocyte metal concentrations in early pregnancy—cross-sectional analysis in Project Viva. Issue 2 (26th May 2021) - Lin, Pi-i D; Cardenas, Andres; Rifas-Shiman, Sheryl L; Hivert, Marie-France; James-Todd, Tamarra; Amarasiriwardena, Chitra; Wright, Robert O; Rahman, Mohammad L; Oken, Emily
ABSTRACT: Background: Dietary sources of metals are not well established among pregnant women in the United States. Objective: We aimed to perform a diet-wide association study (DWAS) of metals during the first trimester of pregnancy. Methods: In early pregnancy (11.3 ± 2.8 weeks of gestation), 1196 women from Project Viva (recruited 1999–2002 in eastern Massachusetts) completed a validated FFQ (135 food items) and underwent measurements of erythrocyte metals [arsenic (As), barium, cadmium, cesium (Cs), copper, mercury (Hg), magnesium, manganese, lead (Pb), selenium (Se), zinc]. The DWAS involved a systematic evaluation and visualization of all bivariate relations for each food–metal combination. For dietary items with strong associations with erythrocyte metals, we applied targeted maximum likelihood estimations and substitution models to evaluate how hypothetical dietary interventions would influence metals' concentrations. Results: Participants' mean ± SD age was 32.5 ± 4.5 y and prepregnancy BMI was 24.8 ± 5.4 kg/m 2 ; they were mostly white (75.9%), college graduates (72.4%), married or cohabitating (94.6%), had a household income >$70, 000/y (63.5%), and had never smoked (67.1%). Compared with other US-based cohorts, the overall diet quality of participants was above average, and concentrations of erythrocyte metals were lower. The DWAS identified significant associations of several food items with As, Hg, Pb, Cs, and Se; for example, As was higher for each SD increment in fresh fruit (11.5%; 95% CI: 4.9%, 18.4%), white rice (17.9%; 95% CI: 9.4%, 26.9%), and seafood (50.9%; 95% CI: 42.8%, 59.3%). Following the guidelines for pregnant women to consume ≤3 servings/wk of seafood was associated with lower As (−0.55 ng/g; 95% CI: −0.82, −0.28 ng/g) and lower Hg (−2.67 ng/g; 95% CI: −3.55, −1.80 ng/g). Substituting white rice with bread, pasta, tortilla, and potato was also associated with lower As (35%–50%) and Hg (35%–70%). Conclusions: Our DWAS provides a systematic evaluation of diet–metals relations. Prenatal diet may be an important source of exposures to metals.